A review of the leafhopper genus Scaphoideus (Hemiptera: Cicadellidae: Deltocephalinae) from Guangxi of China, with description of one new species - Wen, Chao; Chen, Fangying; Dai, Wu (Zootaxa, 2017)
Guangxi Zhuang Autonomous Region is one of the China’s richest regions in terms of biodiversity. Previously, only five species of the genus Scaphoideus Uhler have been reported from Guangxi. Here fifteen species of Scaphoideus from Guangxi, including one new species, are recognized: S. exsertus Li, S. albovittatus Matsumura, S. apicalis Li, S. bilineus Li, S. yuani Chen, Dai and Zhang, S. dentaedeagus Li and Wang, S. festivus Matsumura, S. kumamotonis Matsumura, S. maculatus Li, S. nigrigenatus Li, S. nigrisignus Li, S. palingus Li and Dai, S. yingjiangensis Wang and Li, S. zhoui Li and Xing and S. proxaprocessus sp. nov. Two new synonyms are revealed, Scaphoideus pristiophorus Kamitani and Hayashi, 2013 syn. nov., a junior synonym of Scaphoideus apicalis Li, 1999, and Scaphoideus spiculatus Viraktamath and Mohan, June 2004 syn. nov., a junior synonym of Scaphoideus yingjiangensis Wang and Li, March 2004. The new species is described, and photographs of external habitus and male genitalia of all the species treated are also given along with a key to the species of the region.